2012
DOI: 10.5194/hess-16-4361-2012
|View full text |Cite
|
Sign up to set email alerts
|

Estimating field-scale soil water dynamics at a heterogeneous site using multi-channel GPR

Abstract: Abstract. We explore the feasibility to quantify the fieldscale soil water dynamics through time series of GPR (ground-penetrating radar) measurements, which bridge the gap between point measurements and field measurements. Working on a 40 m × 50 m area in a heterogeneous agricultural field, we obtain a time series of radargrams after a heavy rainfall event. The data are analysed to simultaneously yield (i) a three-dimensional representation of the subsurface architecture and (ii) the total soil water volume b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…as shown in Table 1. Since soil porosity of the top layer is relatively easy to obtain by soil coring, θs is assumed to be known beforehand in the evaluation of the GPR observations of the mean soil water content and reflector depth of the interface (e.g., Pan et. al., 2012a Table 2 for all studied cases.…”
Section: Simulation Model and Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…as shown in Table 1. Since soil porosity of the top layer is relatively easy to obtain by soil coring, θs is assumed to be known beforehand in the evaluation of the GPR observations of the mean soil water content and reflector depth of the interface (e.g., Pan et. al., 2012a Table 2 for all studied cases.…”
Section: Simulation Model and Setupmentioning
confidence: 99%
“…Quantitative observations of soil architecture and soil water content became viable during the past decade using geophysical methods. In particular, ground-penetrating radar (GPR) has been used for efficiently imaging of soil water content distribution (e.g., Huisman et al, 2003;Weihermüller, et al, 2007) and together with soil architecture (Gerhards et al, 2008;Bradford, 2008;Pan et al, 2012a;Klenk et al, 2016). In view of informative multi-dimensional water flow containing in the time-lapse spatial observations of GPR measurements, the common problem of insufficient data information from 1D observations is mitigated for inverse modeling of soil water dynamics in the vadose zone soils.…”
Section: Introductionmentioning
confidence: 99%
“…The non-invasive character of GPR offers the mobility needed to map soil water content of large areas (up to 500 m × 500 m a day) [3]. GPR method for measuring soil moisture is widely used in irrigation experiments [4], monitoring soil moisture dynamic [5][6][7], agriculture [8][9][10], and observation of long time series [11,12]. FO method, CMP method, and Wide angle reflection and refraction (WARR) method are the three commonly used methods of GPR.…”
Section: Introductionmentioning
confidence: 99%
“…Gerber et al (2010) demonstrated that a small layer thickness (20 to 30 cm) can be detected by GPR. A further GPR study by Pan et al (2012) measured the water content on a heterogeneous field site. They found plant water stress reduction of biomass related to structural heterogeneity.…”
mentioning
confidence: 99%